Addition of extra DNA sequences to simian virus 40 DNA in vivo. - Yoshike, K (1977)
The possible addition of extra sequences to simian virus 40 (SV40) DNA was analyzed by electron microscopy in two different cell systems, productively infected monkey cells and activated heterokaryons on monkey and transformed mouse 3T3 cells. We found that the closed circular DNA fraction, extracted from monkey cells at 70 h after infection with nondefective SV40 at a multiplicity of infection of 6 PFU/cell, contained oversized molesules (1.1 to 2.0 fractional lengths of SV40 DNA) constituting about 8% of the molecules having lengths equal to or shorter than SV40 dinner DNA. The oversized molecules had the entired SV40 sequences. The added DNA was heterogeneous in length. The sites of addition were not specific with reference to the EcoRi site. These results suggest that recombination between monkey and SV40 DNAs or partial duplication of SV40 DNA occurs at many sites on the SV40 chromosome. The integrated SV40 DNA is excised and replicates in activated heterokaryons. In this system, besides SV40 DNA we found heterogeneous undersized and oversized molecules containing SV40 sequences in the closed circular DNA population. Additions differeing in size appeared to be overlapping and to have occurred at a preferential site on the SV40 chromosome. These results support the hypothesis that host DNA can be added to SV40 DNA at the site of integration at the time of excision.